“Mistakes help us improve”: Beliefs of high school students on English language learning - Wilang, Jeffrey; Anthoney, Jebamani; Sulankey, Alvina (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2025)
This study examines high school students' beliefs about studying English, particularly their perceptions of language intelligence, aptitude, and age sensitivity in language learning. A total of 87 Year 12 students from a boys' school in Northeastern Thailand voluntarily participated in a pre- and post-intervention online language mindset questionnaire adapted from Lou and Noels' Language Mindset Inventory and wrote a reflective journal to capture their insights on English language learning. The intervention, the Language Mindset Toolkit, was a structured program designed to promote a growth mindset in language learning through six sessions primarily conducted in English with Thai subtitles. The quantitative results indicated that students maintained strong growth-oriented beliefs regarding language intelligence and aptitude, with only minor and statistically insignificant changes after the intervention. However, beliefs about age sensitivity in language learning declined, suggesting that students became more aware of potential challenges in learning languages at different life stages. Despite minimal quantitative shifts, qualitative findings revealed that students valued encouragement, self-efficacy, and the role of mistakes in learning. Many students reported increased confidence and motivation, reinforcing that growth mindset principles contribute to resilience and engagement in language learning. The study highlights the need to continuously reinforce growth mindset principles through instructional practices and teacher feedback. Future research should explore long-term interventions and contextual factors that influence students’ language mindset development, particularly in multilingual educational settings where language learning challenges vary widely.